Case Report: Management and follow-up of continuous positive airway pressure in a Fontan patient with obstructive sleep apnea - Andrew Ligsay; Colin Crilly; Conor P. O'Halloran; Philip Thrush (Frontiers in Pediatrics, 2026)
Patients with single ventricle heart disease undergo staged surgical palliation ultimately resulting in total cavopulmonary anastomosis (Fontan procedure), with circulation that relies on passive pulmonary blood flow. In Fontan patients with comorbid obstructive sleep apnea (OSA), previous reports have suggested that continuous positive airway pressure (CPAP) therapy can be detrimental and negatively affect cardiac function in this population. However, we describe a case of an adult Fontan patient with ventricular dysfunction and severe OSA who demonstrated significant improvement his cardiac index following CPAP use. This case highlights a potential subset of patients with Fontan physiology who may derive significant cardiovascular benefit from CPAP therapy.